Extraction of Bioactive Macromolecules Using Supercritical Carbon Dioxide Technology - Dong, Zhijun; Xia, Weitian (Transactions on Environment, Energy and Earth Sciences, 2024)
The complex structure of biological macromolecules makes it play an important role in various fields, and its demand is increasing day by day, so its extraction technology has also become a hot research object. For example, essential oils can be able to extract from different parts of plants. Because they are rich in a variety of special chemical groups, they endow them with unique physical and chemical properties, making them widely used in various fields. Conventional extraction methods, such as steam distillation, cold pressing and solvent extraction, all have certain limitations and disadvantages for extracting essential oils. And with the intensification of the greenhouse effect, how to use carbon dioxide (CO2) has become a hot and urgent topic. The supercritical CO2 extraction technology is to turn CO2 into treasure and use it rationally. The use of supercritical CO2 extraction has higher efficiency, lower energy consumption and other outstanding advantages. This research focuses on the analysis of the extraction rate of biologically active macromolecules by supercritical CO2 extraction technology, including essential oils and Angelica. The effects of different experimental parameters on the extraction results were explored, the reasons were analyzed, and appropriate extraction conditions were obtained to optimize the extraction rate.